Breaking free from the crystal lattice: Structural biology in solution to study protein degraders. (April 2023) - Haubrich, Kevin; Spiteri, Valentina A.; Farnaby, William; Sobott, Frank; Ciulli, Alessio
Abstract: Structural biology offers a versatile arsenal of techniques and methods to investigate the structure and conformational dynamics of proteins and their assemblies. The growing field of targeted protein degradation centres on the premise of developing small molecules, termed degraders, to induce proximity between an E3 ligase and a protein of interest to be signalled for degradation. This new drug modality brings with it new opportunities and challenges to structural biologists. Here we discuss how several structural biology techniques, including nuclear magnetic resonance, cryo-electron microscopy, structural mass spectrometry and small angle scattering, have been explored to complement X-ray crystallography in studying degraders and their ternary complexes. Together the studies covered in this review make a case for the invaluable perspectives that integrative structural biology techniques in solution can bring to understanding ternary complexes and designing degraders. Graphical abstract: Image 1 Highlights: Targeted protein degradation relies on small molecules that induce often dynamic and conformationally heterogeneous complexes. Crystallography offers high resolution data to guide molecule design but may give an incomplete view of heterogenous systems. In solution techniques offer orthogonal insights that improve understanding of these complexes to facilitate degrader design.